Phenotypic characteristics of indigenous dairy buffaloes of Bangladesh - Md O. Faruque; Abdullah I. Omar; Y. Zhang; Md Mohsin T. Raju; Sahed Hossain (Revista Científica)
The utility of buffalo in Bangladesh has shifted from draught to dairy. People of Bangladesh are now aware of outstanding food value of buffalo milk and meat. However, the market share of buffalo milk and meat is very low compared to cattle milk and meat as evidence from the number of buffalo and cattle. Bangladesh possesses 0.64 million buffaloes and 295 million cattle. Dairy buffalo of the country has no recognized breed and is indigenous river type. In absence of animal identification and recording system, actual lactation period and yield of dairy buffalo is unknown. This study was, therefore, done to find out actual lactation period and yield as well calving interval of indigenous dairy buffaloes in Bangladesh based on animal recording. 384 indigenous dairy buffaloes having 3 rd and 4th parity in 7 herds managed under traditional system in two agro-ecological zones covering 4 seasons was subjected to this study. All the cows and calves were ear tagged, date of calving and milk yield was recorded following International Committee for Animal Recording (ICAR) (2017). The actual lactation period, actual lactation yield and calving interval were found out from the record. 300-day lactation yield was calculated after ICAR (2017). Data was analyzed after R statistics to find out the differences among various effects on production. The actual lactation period and actual lactation yield were 267.28±0.68 days and 749.36 ±15.08 kg, respectively whereas 300-day lactation yield was 766.92±15.32 kg. The minimum, maximum and average dry period were 74 days, 303 days and 185+2.55 days. The minimum, maximum and average calving interval were 369 days, 547 days and 453+5.64 days. Lactation period, lactation yield and calving interval were affected significantly by genotype, herd, season and agro-ecological zone. The results indicate that there is wide variation in lactation period, lactation yield and calving interval. This property can be utilized in practicing selective breeding for genetic improvement of indigenous dairy buffaloes in Bangladesh.